2019
DOI: 10.1186/s13068-019-1472-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel thermostable chitinolytic machinery of Streptomyces sp. F-3 consisting of chitinases with different action modes

Abstract: Background The biodegradation of chitin is an important part of the carbon and nitrogen cycles in nature. Speeding up the biotransformation of chitin substrates can not only reduce pollution, but also produce high value-added products. However, this process is strictly regulated by the catalytic efficiency of the chitinolytic machinery. Therefore, it is necessary to study the mode of action and compound mechanisms of different chitin-degrading enzymes in depth to improve the catalytic efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Yet, the rate and efficiency of chitin degradation appear to differ strongly among chitinolytic bacterial species (Bai et al ., 2016). The actinobacteria are supposed to be the most effective chitin degraders in the terrestrial ecosystem with an extensive set of chitinolytic enzymes (Lacombe‐Harvey et al ., 2018; Sun et al ., 2019). In general, most bacterial chitinases belong to monospecific family GH18, whereas the occurrence of chitinases belonging to the other monospecific chitinase family GH19 is less common (Nguyen et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the rate and efficiency of chitin degradation appear to differ strongly among chitinolytic bacterial species (Bai et al ., 2016). The actinobacteria are supposed to be the most effective chitin degraders in the terrestrial ecosystem with an extensive set of chitinolytic enzymes (Lacombe‐Harvey et al ., 2018; Sun et al ., 2019). In general, most bacterial chitinases belong to monospecific family GH18, whereas the occurrence of chitinases belonging to the other monospecific chitinase family GH19 is less common (Nguyen et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…3). In detail, chitinolytic genes of Ewingella americana 193 resemble the system of chitinolytic actinobacteria, except for the lack of the lytic monooxygenase AA10 (Lacombe‐Harvey et al ., 2018; Sun et al ., 2019). Our other strains possessed a less complex set of chitinolytic genes, but as for Ewingella americana we detected genes for endo‐cleaving enzymes: endochitinase (CH18, CH19) and chitosanases (GH5 and GH8), exohydrolases: β‐N‐acetylglucosaminidase (GH3, GH5 and GH20) and β‐glucoseaminidase (GH2 and GH9).…”
Section: Discussionmentioning
confidence: 99%
“…Chitin is the main structural component of cell wall of fungus and invertebrates exoskeletons like insects and crustaceans [4]. With advancement, it has been shown that chitin and its derivatives are of pharmaceutical and other industrial importance [5]. Because of its various applications, it has got immense attention in the field of pharmacology, agriculture and biotechnology [6].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the most routine approach for obtaining microbial chitinases is culturing the chitinolytic microorganisms first, and then obtaining their (heterologously) expressed chitinases, such as the chitinases: SsChi18A, SsChi18B, and SsChi18C from Streptomyces sp. F-3 [6], CmChi1 from Chitinolyticbacter meiyuanensis SYBC-H1 [7], MtCh509 from Microbulbifer thermotolerans DAU221 [8] , PbChi74 from Paenibacillus barengoltzii [9], etc. However, it is well known that the vast majority (up to 99-99.9%) of microorganisms present in nature, especially those in the extreme environments, cannot be cultured under laboratory conditions, which is one of the biggest obstacles to discover the novel enzymes/chitinases [10].…”
Section: Introductionmentioning
confidence: 99%